Exploring the effects of a nonhydrostatic dynamical core in high‐resolution aquaplanet simulations. Issue 6 (21st March 2017) - Yang, Qing; Leung, L. Ruby; Lu, Jian; Lin, Yuh‐Lang; Hagos, Samson; Sakaguchi, Koichi; Gao, Yang
Abstract: This study explores the impact of a nonhydrostatic dynamical core in high‐resolution regional climate simulations using an aquaplanet framework. The Weather Research and Forecasting (WRF) model is used to conduct simulations with both hydrostatic (H) and nonhydrostatic (NH) solvers at horizontal grid spacings (Δ x ) of 36, 12, and 4 km. The differences between the H and NH simulated precipitation (Δ P ) are notable even at Δ x  = 12 km in the intertropical convergence zone and the transition region to the drier subtropics. At gray zone grid spacing (12 km and 4 km) over the tropics, Δ P is sensitive to whether a cumulus parameterization scheme is used or not. With an idealized Witch of Agnesi land mountain, differences in the precipitation and circulation (vertical velocity) between the H and NH simulations are significant even at Δ x  = 36 km in the tropics due largely to the strong feedbacks related to moist processes. The differences increase as the model grid spacing and mountain half width ( a ) are reduced, accompanied by a shift toward a more nonhydrostatic flow regime at a  = 24 km. Latent heat release drastically enhances the differences between the NH and H simulations and extends the effect of nonhydrostatic dynamics to a broader region over the mountain and downstream over the tropics. Overall, differences exist between H and NH simulations even at resolutions between 12 and 36 km, but the differences are sensitive to the representations of moist physics and other features such as horizontal diffusion used in the WRF model. Key Points: The effect of nonhydrostatic dynamics is amplified by moist processes and associated latent heating The effect of nonhydrostatic dynamics is sensitive to model physics parameterizations Differences between hydrostatic and nonhydrostatic WRF simulations are nonnegligible at Δ x = 12 km and 36 km with tropical mountains